A legal analysis on marital rape in Malaysia / Muhammad Syafiq Mohd Sahar, Mohamad Arif Aizuddin Masrom and Mohamad Zakwan Mohamad Anuar - Mohd Sahar, Muhammad Syafiq; Masrom, Mohamad Arif Aizuddin; Mohamad Anuar, Mohamad Zakwan (Faculty of Law, 2008)
The purpose of this research is to analyze the issue of marital rape in Malaysia from the legal perspective. In the first phase of the project, we discuss the current law and situation of marital rape in Malaysia. Then, we compare the law with other countries that have applied it such as Scotland and United States. The second phase of the project, we carried out field work in the context that we handle questionnaires to the respondents that relates to this issue and to the public in order to receive their feedback. The final phase of this project is where we conclude our research and recommend solutions that can be done by the legislature and authorities in Malaysia in order to handle this issue efficiently.